Comparability of Estimates of the Industrial Distribution of Employment - Henderson, John P. (The Review of Economics and Statistics, 1961)
SINCE about I950 the Bureau of Labor Statistics has been publishing a monthly series showing the industrial distribution of the employed nonfarm labor force.' In addition to supplying current estimates on nonagricultural employment, the figures have been compiled from I9I9 and yield, therefore, a continuous forty-year series on the changing pattern of the industrial distribution of employment.2 major value of this series is in evaluating current employment trends, serving as an important supplement to the Census Bureau's monthly estimate of aggregate employment. BLS figures can also be used effectively to study the changing industrial pattern of employment.3 BLS estimates have several distinct advantages over the usual statistical series used to evaluate long-run changes in employment patterns. Typically such series rely exclusively upon decennial data, to the exclusion of either monthly or yearly figures on the industrial composition of the work force.4 major weakness in such a dependence stems from the obliteration of cyclical changes in the industrial composition of employment, and what may be only short-run changes can too easily be interpreted as long-run movements.5 For example, decennial data for I930-50 show that there has been a long-run increase in employment in the tertiary industries, and this fits the pattern which Colin Clark and others hypothesize.6 However, yearly data on employment patterns, such as those of the BLS, indicate that there is considerable cyclical movement in the industrial composition of employment, with the result that service occupations rise as a percentage of total employment in recessions or periods of less than full employment. Each of the recent Census years (I930, I940, and I950) had a sizeable portion of unemployment, and it is by no means clear that the long-run trend of the tertiary industries is entirely consistent with the industrial pattern that emerges when decennial data are used. However, it is not the purpose of the present paper to discuss the degree to which decennial data are truly indicative of long-run trends, nor to evaluate the effectiveness of BLS data for estimating short-run movements. present intent is merely to contrast the industrial distribution of employment obtained from BLS data with two distributions derived from the decennial data. More specifically, the distribution derived from BLS figures is compared with two estimates prepared by researchers associated with the National Bureau of Research. First, the Carson-Barger estimates for the labor force7 and, second, John W. Kendrick's more recent employment figures for the industrial distribution 8 are juxtaposed with BLS figures. Both the Carson-Barger and the Ken'Bureau of Labor Statistics, United States Department of Labor, Handbook of Labor Statistics, 1950 Edition, Bulletin ioi6 (Washington, 1950), I-5; Measurement of Industrial Employment, Monthly Labor Review, 76 (September 1953), 968-73. 2 Bureau of Labor Statistics, Department of Labor, and Earnings, Annual Supplement (June 1958). 'Ewan Clague, The Shifting Industrial and Composition of the Work Force During the Next Ten Years, Daily Labor Report (Washington, 1958), Thursday, January i6, 1958, Special Supplement, i-II; reprinted in Monthly Labor Review, 8I (July 1958), I676-9I. ' Cf. Simon Kuznets, Quantitative Aspects of the Growth of Nations, III. Industrial Distribution of National Product and Labor Force, Development and Cultural Change, vi (July 1957), 19-32; Colin Clark, Conditions of Progress (3rd ed., New York, 1957); P. Whelpton, Occupational Groups in the United States, I820I920, Journal of the American Statistical Association (September I926), 335-43; and Daniel Carson, Changes in the Industrial Composition of Manpower Since the Civil War, Studies in Income and Wealth, Vol. xi (New York, I949), 46-I34. For an instance of such misinterpretation, see George Stigler, Trends in Employment in the Service Industries (Princeton, 1956). 6 Colin Clark, Conditions of Progress (London, 1957) ; and A. G. B. Fisher, Economic Implications of Material Progress, International Labour Review, LVII (July